P183 Can a multidisciplinary approach to the investigation of patients referred with haemoptysis be both cost effective and safe?. (December 2018) - Miller, R; Higbee, DH; Foster, S; Anning, L; Fox, D
Abstract : Introduction: In 2015, Taunton and Somerset NHS Trust introduced a weekly diagnostic lung multidisciplinary team (MDT) meeting of respiratory physicians and radiologists. Previously all patients referred as a two-week wait (2WW) had a CT Chest/Abdomen/Pelvis (CT CAP), then respiratory outpatient appointment (OPA) and bronchoscopy, regardless of chest X-ray (CXR) findings. The diagnostic MDT reviews all 2WW referrals to decide further investigation. For those with haemoptysis and a normal CXR, it was proposed that a more limited CT scan was sufficient and that further review was unnecessary if CT was unremarkable. Methods: Diagnostic lung MDT cases from 2016 and 2017 were reviewed (n=385). Cases where the CXR and/or CT request included 'haemoptysis' were further examined. Those with radiologist-reported normal CXRs were included in this dataset (n=61, 15.8%). Electronic records were reviewed to ascertain further investigations and eventual diagnosis. Based upon the current tariffs for New Patient Respiratory OPAs, bronchoscopy and CT scans, 1 financial savings compared with the old pathway were calculated. Results: Of the 61 patients, none were subsequently diagnosed with a lung malignancy. Only nine patients (14.8%) had a full CT CAP, with 44 having CT Abdo/Pelvis (CT AP) with contrast and eight having High-Resolution CT (HRCT), saving £584. Outpatient review occurred for 54 patients (88.5%), saving £1456. The most significant financial saving was in bronchoscopy, which only 13 (21.3%) patients underwent, saving £23 280. The overall cost saved by the diagnostic MDT was £25 320. Conclusion: Replacing a standard investigation pathway with the diagnostic lung MDT has proved safe and cost-effective, with no cases of missed cancer. Additional savings could be made by further selecting those requiring outpatient review and by favouring HRCT over CT AP as the choice mode of imaging. As well as being cheaper, HRCT benefits patients by lowering radiation dose and eliminating the risks of intravenous contrast (anaphylaxis, renal injury). Reference: 1. Allen M. Respiratory Coding and Tarriff Update 2017/8. British Thoracic Society April 2017. https://www.brit-thoracic.org.uk/document-library/delivery-of-respiratory-care/coding/respiratory-coding-and-tariff-update-2017–2018/